Control of experimental inflammatory bowel disease by regulatory T cells - Asseman, C; Fowler, S; Powrie, F (2000)
A helper T cell type 1-mediated colitis driven by enteric bacteria develops in severe combined immunodeficient mice after transfer of CD45RB(high)CD4(+) T cells. Development of disease can be prevented by cotransfer of the reciprocal CD45RB(low) subset. Analysis of the mechanism of immune suppression transferred by CD45RB(low)CD4(+) cells revealed essential roles for both IL-10 and TGF-beta. These data indicate that a functionally specialized population of regulatory T (Treg) cells exists in normal mice and that these can prevent the development of pathogenic responses toward commensal bacteria. The role of Treg cells in the control of the immune response is discussed.